TOTAL PHYSICAL RESPONSE IN LEARNING NARRATIVE READING FOR YOUNG LEARNERS TO IMPROVE RECEPTIVE VOCABULARY - Sulistyani, Yulin (Jurnal Inovasi Global, 2023)
This study aims to analyze the effectiveness of the Total Physical Response Strategy (TPR) in learning narrative reading for young learners to improve receptive vocabulary in elementary school students. To achieve the goal of the study, the study used a quasi-experimental design, involving two groups of participants (control and experimentation) of third-grade students at an Islamic Elementary School in Kediri as well as providing pretest, treatment, and posttest. In addition, observations by conducting field records were conducted to determine the response of the students to the TPR Strategy. Data analysis showed that the results of the pretest and posttest scores of the control groups showed no significant difference. Hence it can be concluded that the mastery of English vocabulary of the experimental group increased significantly. In addition, data from observations by conducting field records showed that students generally responded well to the use of the TPR Strategy in learning activities. This is demonstrated by the learning process, the students look happy, and enthusiastic, and participate well without any feelings of stress or stress. Moreover, they understand both the learning material and the instruction in the classroom. Thus it can be concluded that the TPR Strategy is effective and suitable for use in learning narrative reading for young learners